Penggunaan Maskot Sebagai Media Pendukung Untuk Kegiatan Promosi di Wisata Agro Lembah Kecubung - Nathaniela Sabitah Haq; Diana Aqidatun Nisa (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This community service was carried out in Penanggungan Village, Trawas District, Mojokerto Regency. Penanggungan Village is one of the tourist villages in Mojokerto Regency and one of the tourist attractions owned by Penanggungan Village is Lembah Kecubung Agrotourism. The problem faced by the manager is the lack of a promotion strategy. The solution that can be done is to do branding to help improve the image of Amethyst Valley Agrotourism, one of which is by designing a mascot.